Security in the Realm of Social Justice: From Processes to the Emergence A Critical Look at Justice and National Security - Salman Sadeghizadeh; Abdulamir Nabavi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Demand for security is the second most essential human need after the physiological necessities to the life which evolves along with the metamorphoses in common life trends and processes and has gotten different aspects. In the modern age, the plaint concept - or an afloat signifier from a postmodernist perspective - of security in the epistemological context created from the classic discourse of national security was related to a signified which was neither inclusive to all the members nor exclusive to the aliens. The mentioned shortage has been fixed through the new articulation of concepts and creation of a new conceptual correlation between the security and justice under a new epistemology embedded in the societal security discourse. In fact, the concept of national security could serve the sustainable security so long as it succeeds to create and insure justice in all societal fields along with boosting the social capital by which the convenience of individuals and social groups is reachable. To do so, adopting a society-based approach instead of a power-based one is necessary. This main is feasible and reachable only by prioritizing the civil society, empowering the society-founded institutions and embedding the policy making in the social and cultural values.